Analysis of Focused Attention Levels in Science Learning among Children with Hyperactivity: A Study in a Special Education Setting - Ardianti, Sekar Dwi; Sumaji; Evanita; Supratiwi, Mahardika; Wanabuliandari, Savitri; Tanghal, Analiza B (Jurnal Pendidikan IPA Indonesia, 2025)
The objectives of this study were: (1) to analyse the characteristics of focused attention behaviour during science learning in ADHD students; (2) to identify learning strategies implemented by teachers to improve focused attention in ADHD students; and (3) to analyse the improvement of focused attention. The method used was the Mix Method Sequential Exploratory. This study was conducted at the Sunan Kudus Special Elementary School (SES). Data collection was conducted through observation and interviews. The research instruments were observation sheets and interview sheets. Qualitative data analysis was conducted using the Miles and Huberman model, while quantitative data were analysed using t-tests and n-gain tests. The results of the study indicate that the characteristics of the focused-attention pattern among ADHD students are that they always respond to distractions in their learning environment. Students can complete assignments, but are unable to avoid distractions in their surroundings, which often disrupts their focused attention. The learning strategy implemented involves the teacher developing several practical approaches, intuitively and contextually, to manage student attention during learning. Science learning is designed to activate students in observation and discussion activities. The results of the t-test show a t value of -12.0, which is smaller than 0.05, indicating a difference in the focus of student attention before and after science learning with the teacher-implemented strategies. The results of the group N-Gain analysis show an average N-Gain obtained of 0.103, which is in the low category. This low N-Gain value confirms that the learning intervention has not produced substantial improvements in student attention and focus, indicating that more varied and contextual learning strategies are needed.